Species composition of Ostracoda in the Okinawa islands, and geographical distribution of the two genera \(Loxoconcha\) and \(Xestoleberis\) (Arthropoda: Crustacea) around Japan - Le, Doan Dung; Tsukagoshi, Akira (Vietnam Journal of Marine Science and Technology, 2023)
This study was conducted in the period of 2012 to 2015 in some locations of Japan. At each location, samplings were carried out on reef slopes using SCUBA diving, on reef flats, tidal beaches and river mouths during low tide. The specimens then were treated using a differential interference contrast microscope with a camera lucida (BX-50, OLYMPUS), a quick auto-coater (JFC-1500, Ion Sputtering Device), a scanning electron microscope (SEM) in the laboratory of Shizuoka University,… The result shows that total 139 species of recent ostracoda belonging to 28 families, 70 genera recorded in the Okinawa Islands, southern Japan are found. Most diversified families include Loxoconchidae (26 species - 18.7%), Xestoleberididae (17 species - 12.2%), Bairdiidae (13 species - 9.4%), Hemicytheridae (13 species - 9.4%), Leptocytheridae (8 species - 5.8%). Based on the distributional pattern of pore systems located below the eye tubercle of Loxoconcha and the types of pores on carapaces of Xestoleberis, the species groups of the two genera were divided into three groups, i.e., Groups A, B and C. Geographical distribution of three species groups was shown for each location in the present report. The geographical distribution of three species phylogenetic groups (i.e. Groups A, B and C) of the two genera Loxoconcha and Xestoleberis suggests that the fauna of two genera in the Okinawa islands are more similar to southern faunas (e.g., Vietnam, Philippines, Australia,…) than Japanese Island Arc fauna. Hence, the origin of two genera Loxoconcha and Xestoleberis in the Okinawa islands, southern Japan may be from the South.